Thermal and mass diffusion on MHD natural convective flow of a rarefied gas along vertical porous plate - Ram P.C.; Nath R.; Agrawal A.K. (My University, 2025)
The flow of an electrically conducting incompressible rarefied gas due to the combined buoyancy effects of thermal and mass diffusion past an infinite vertical porous plate with constant suction has been studied in the presence of uniform transverse magnetic field. The problem has been solved for velocity, temperature, and concentration fields. It has been observed that mean velocity and the mean temperature are affected by the Grashof numbers G1 and G2, the slip parameter h1, temperature jump coefficient h2, concentration jump coefficient h3 and magnetic field parameter M. The amplitude and the phase of skin-friction and the rate of heat transfer are affected by frequency in addition to the above parameters. They are shown graphically. The numerical values of the mean skin-friction and the mean rate of heat transfer are also tabulated. © 1984 D. Reidel Publishing Company.